Numerical simulations of a low-speed radial fan. (1st January 2012) - Sanjose, Marlene; Moreau, Stéphane
Steady and unsteady Reynolds-averaged Navier-Stokes simulations have been achieved on a 3D centrifugal blower, typical of residential ventilation systems, installed in a volute including both tip clearance and flow leakages. The grid topology is found critical to predict global performances accurately and to preserve unsteady flow features necessary for future accurate acoustic predictions. A grid density larger than ten million cells is also required to correctly predict torque and static efficiency and to resolve flow recirculation and pressure losses in the blade passage. The turbulence model has a minor effect on the global performances of the machine. Both fluent and CFX yield similar overall performances even though local flow features differ and more asymmetry are obtained in the scroll with CFX. Finally, significant differences are observed between steady and unsteady simulations. Only URANS can provide a realistic fan interaction with the volute tongue.